The civil war hardship on al-Anbar community of Iraq - Riyadh, Ibrahim A.J; Novel Anak Lyndon, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Life after the civil war between Sunni and Shiite has not only changed the infrastructure and situation of Al-Anbar Province, Iraq in 2013, but also it has brought social change and affected their belief system. As many people were killed, losing their families and home; people are also suffered of losing their confidence to lead a new life and it includes the shattered belief system. Indirectly, they are still suffering from the subsequences of the war even though not all has actually involved in the civil war. The objective of this study is to understand the impact of the civil war towards the society, to explore the hardship and obstacle facing by them after the civil war. This objective will be discussed mainly under the concept of social change and belief system. Al-Anbar province has been chosen for the location to be studied since it showed the highest numbers of killing, destruction, displacement, deterioration of the political situation as well as dissension among people of the same religion. The research is based on a qualitative study in which an in-depth interview will be conducted. The study includes twenty-four male informants. The data was transcribed and translated from Arabic language into English and thematic analysis was used too. The finding shows that majority of the informants believed that the religious belief in the community is strongly affected by the civil war. Most informants cited instant increase in the level of commitment towards Islam. In the face of intense danger, prayers performed more frequently than usual as believers turned to God for protection and seeking His answer in the period of adversity. Local mosques organized additional gatherings and talks to help to preserve unity among people and strengthen their integrity in faith amidst rising sectarian tension between Shiite and Sunni Muslims. As the result, civil war has created both optimist and pessimist people depending on how they have taken the new social changes that have taken place and how the new situations will shape their understanding towards their belief system.